The Influence of Promotions and Prices on Ticket Purchase Decisions at the Cultural Lens Vol. 2 Event at Dimigo Pool Medan 2024 - Fauzan, Diaz Ibnu; Pasaribu, Ika Mary (Journal of Economics and Social Sciences (JESS), 2025)
ultural Lens Vol.2 is one of the special events held in the city of Medan, in commemoration of Nusantara Day which falls on December 13, the organizers have the motivation and inspiration to create a cultural event which adds to the insight of visitors that there are many cultures, customs, traditional clothes and traditional dances ranging from Batak, Javanese, Malay, Tiong Hoa and Indian cultures. This event will be held on December 14, 2025 located at Dimigo Pool Medan. Based on internal data of 1,000 visitors who bought tickets, but the organizers only got 233 visitors who bought tickets, this phenomenon shows that the organizers have not been able to achieve the target and there must be an evaluation to create space to improve this. Promotions and Prices are 2 of the many factors that affect the Decision to Buy tickets for the Cultural Lens Vol.2 event. This study aims to find out whether promotions and prices affect the decision to purchase tickets for the Cultural Lens Vol.2 event. This study uses a quantitative method with data collection carried out through questionnaires and literature studies. The data results will be analyzed using data quality tests, classical assumption tests, multiple linear analysis, determination coefficient tests and hypothesis tests with a total of 70 respondents. The results of this study show that promotions and prices partially and simultaneously have a positive and significant effect on ticket purchase decisions at the Cultural Lens Vol.2 event. The results of the determination coefficient test (R2) showed that promotions and prices were able to influence the purchase decision of Cultural Lens Vol.2 event tickets by 65.7% and the remaining 34.3% could be explained by factors not studied in this study.